2020
DOI: 10.1101/2020.05.18.102343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resistance to pirimiphos-methyl in West AfricanAnophelesis spreading via duplication and introgression of theAce1locus

Abstract: Vector population control using insecticides is a key element of current strategies to prevent malaria transmission in Africa. The introduction of effective insecticides, such as the organophosphate pirimiphos-methyl, is essential to overcome the recurrent emergence of resistance driven by the highly diverse Anopheles genomes. Here, we use a population genomic approach to investigate the basis of pirimiphos-methyl resistance in the major malaria vectors Anopheles gambiae and A. coluzzii. A combination of copy … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Control of insecticide-resistant vector populations is predicated on a clear understanding of the complex interplay between molecular mechanisms and fitness costs which contribute to mosquito behavior, phenotype and vectorial capacity, the genetic and local environmental factors driving ongoing resistance selection, and the implications of resistance for intervention operational efficacy. Substantial progress has been made elucidating key target site mutations ( 4 7 ), overexpression of detoxification enzymes ( 8 12 ) and alternate gene families and pathways ( 13 17 ), all of which play important roles in resistance modulation. Furthermore, the recent publication of genome data for more than 1,000 Anopheles ( An .)…”
Section: Introductionmentioning
confidence: 99%
“…Control of insecticide-resistant vector populations is predicated on a clear understanding of the complex interplay between molecular mechanisms and fitness costs which contribute to mosquito behavior, phenotype and vectorial capacity, the genetic and local environmental factors driving ongoing resistance selection, and the implications of resistance for intervention operational efficacy. Substantial progress has been made elucidating key target site mutations ( 4 7 ), overexpression of detoxification enzymes ( 8 12 ) and alternate gene families and pathways ( 13 17 ), all of which play important roles in resistance modulation. Furthermore, the recent publication of genome data for more than 1,000 Anopheles ( An .)…”
Section: Introductionmentioning
confidence: 99%
“…The G280S/G119S ace -1 mutation, found in high frequencies across Sahel confers organophosphate an carbamates resistance (Weill et al, 2004), and is shown recently to confer resistance to pirimiphos-methyl, in An. coluzzii / gambiae (Grau-Bove et al, 2021). Several mutations found within the VGSC have recently been described/validated.…”
Section: Discussionmentioning
confidence: 99%
“…Different configurations have different fitness costs in the absence of insecticide, and a variant that deletes the 11 other co‐amplified genes but not Ace‐1 (termed ‘adaptive deletion’) is spreading in West Africa and introgressing into the closely related species An. coluzzii 11,12 . In the spider mite Tetranychus evansi , a point mutation in Ace‐1 conferring insensitivity to chlorpyrifos also confers a lower fitness in the absence of the insecticide, which is compensated for by an increase to eight to ten copies in some resistant strains 13 .…”
Section: Ancient and Recent Gene Duplications In Insecticide Resistancementioning
confidence: 99%